Living Proof: Tracing HIV/AIDS Cultural Production in the North East of England - Fiona Anderson (British Art Studies)
This article traces a history of *Living Proof* (1991--92), a collaborative, multidisciplinary arts project produced with diverse communities living with HIV/AIDS across the North East of England. The workshops, exhibitions, and performances produced as part of---and in response to---*Living Proof* engaged directly with racialised and gendered experiences in the United Kingdom of HIV/AIDS care, addiction, the prison system, and the radical power of international solidarity with AIDS activists and cultural producers in North America, including Pomo Afro Homos and the so-called NEA Four. The history of *Living Proof* speaks to the distinctive funding, galleries, and festival and community networks in the region in the late 1980s and early 1990s. It is an overlooked but vital part of UK AIDS histories. This article draws on the project's scattered archive and conversations with those involved, to think critically about what it means to historicise it now, in the midst of an archival turn in HIV/AIDS scholarship, as British art that responded to art and HIV/AIDS in the 1980s and after receives greater scholarly attention, and while health and economic inequalities in the region persist.